2009
DOI: 10.1007/s11914-009-0020-5
|View full text |Cite
|
Sign up to set email alerts
|

Osteoporosis prevention and nutrition

Abstract: Although calcium and vitamin D have been the primary focus of nutritional prevention of osteoporosis, recent research has clarified the importance of several additional nutrients and food constituents. Further, results of calcium and vitamin D supplementation trials have been inconsistent, suggesting that reliance on this intervention may be inadequate. In addition to dairy, fruit and vegetable intake has emerged as an important modifiable protective factor for bone health. Several nutrients, including magnesi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
93
0
2

Year Published

2010
2010
2022
2022

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 126 publications
(96 citation statements)
references
References 53 publications
1
93
0
2
Order By: Relevance
“…The principal physiological function of 1,25(OH) 2 D 3 is enhancing the absorption of calcium and phosphate from the intestinal tract, therefore positively regulating bone formation [9][10][11] . To date, several lines of epidemiological and experimental findings have supported the links of vitamin D with various conditions or diseases beyond bone health [3] , including muscle function [12,13] , autoimmune diseases [14] , cancer [15,16] , cardiovascular diseases (CVD) [17][18][19] , hypertension [20,21] , diabetes [22] , inflammatory diseases [23] , and all-cause mortality [24] , etc.…”
Section: General Roles Of Vitamin D In Physiological Conditions and Dmentioning
confidence: 99%
See 3 more Smart Citations
“…The principal physiological function of 1,25(OH) 2 D 3 is enhancing the absorption of calcium and phosphate from the intestinal tract, therefore positively regulating bone formation [9][10][11] . To date, several lines of epidemiological and experimental findings have supported the links of vitamin D with various conditions or diseases beyond bone health [3] , including muscle function [12,13] , autoimmune diseases [14] , cancer [15,16] , cardiovascular diseases (CVD) [17][18][19] , hypertension [20,21] , diabetes [22] , inflammatory diseases [23] , and all-cause mortality [24] , etc.…”
Section: General Roles Of Vitamin D In Physiological Conditions and Dmentioning
confidence: 99%
“…Bone health osteomalacia, osteoporosis [3] Muscle function muscle weakness [7,8] Autoimmunity multiple sclerosis, Crohn disease, diabetes mellitus, systemic lupus erythematosus, asthma, rheumatoid arthritis, etc. [49][50][51][52][53][54][55][56][57][58][59] Cancer breast, prostate, colorectal, lung, endometrial cancers, etc.…”
Section: Functionsmentioning
confidence: 99%
See 2 more Smart Citations
“…Although tea contains caffeine, levels are relatively low. 109 alcoholism has often been associated with osteoporosis but other studies have shown a protective effect, with a J-shaped dose/response curve with 1-2 drinks per day correlating with improved BMd in postmenopausal women; when stratified by type of alcohol, wine gave the greatest benefit in women and beer in men, while spirits gave the lowest BMd 110 . In vitro studies have also shown that resveratrol is active in osteoblastic MC3t3-e1 cells and may have a synergistic effect with vitamin D in promoting bone health 111 .…”
Section: Calcificationmentioning
confidence: 96%